Bone mineral density in top level male athletes of different sports - Platen, P.; Chae, E. H.; Antz, R.; Lehmann, R.; Kühlmorgen, J.; Allolio, B. (European Journal of Sport Science, 2001)
The purpose of this study was to determine the influence of muscle strength, training-specific and anthropometric parameters on bone mineral density (BMD) in male top athletes of different sports in comparison to untrained controls. BMD was measured by dual energy X-ray absorptiometry in 173 males, aged 18 to 31 years. Of these, 104 were athletes (runners, n = 21; cyclists, n = 12; triathletes, n = 18), heavy athletes (HA, judo and wrestling, n = 28), and team sport athletes (TS, handball, soccer, basketball, volleyball, n = 25); 44 were unspecifically trained sport students (STU); and 25 were untrained controls (UT). Sport- and group-specific differences were found in anthropometric but not strength parameters. Marked sport- and group-specific differences were found for BMD at lumbar spine (LSP) and the femoral sites (FEM). Group-specific effects on BMD were clearest when calculating percentual differences between BMD of athletes and UT: In group I (HA, TS, and STU), BMD at LSP and FEM were significantly (p < .01) higher compared to UT; in group II (R and TRI), BMD at FEM but not at LSP was higher compared to UT (p < .01); and in group III (C), no BMD value was significantly different from UT. Multiple regression analysis revealed lean body mass to be the strongest predictor for BMD at LSP and FEM. We conclude that mechanical loads have strong effects on bone adaptation. Sport-specific and body region-specific effects have to be taken into account for evaluation of osteogenic effects of exercise. Particularly dynamic sports with short, high, and multidimensional loads have the strongest effects on bone formation, independent of training quantity.